Efficacy of hydroalcoholic Petroselinum crispum L. leaf extract on pentylenetetrazole-induced seizure in rats - Zahra Forouzandeh Shahrakei; Ehsan Rahimi; Nahid Jivad (Shahrekord University of Medical Sciences, 2022)
Background and aims: Epilepsy is a disorder of the central nervous system that manifests with sudden, transient, recurrent and unpredictable seizures of sensory-motor, autonomic origin. Drugs used to treat the disorder may cause numerous side effects and treatment response may be unsatisfactory. The purpose of the present study was to investigate the in vitro effects of hydroalcoholic Petroselinum crispum L. leaf extract on pentylenetetrazole (PTZ)-induced seizure in rats.Methods: In this experimental study, 60 male rats were randomly divided into 6 groups of 10 each. Control group received normal saline. Model group received PTZ at 90 mg/kg intraperitoneally. Intervention groups received P. crispum extract at concentrations of 100, 150 and 200 mg/kg 30 minutes before PTZ administration. Positive control group received 40 mg/kg phenobarbital 30 minutes before PTZ injection. Then, seizure threshold was recorded. In addition, serum and brain antioxidant capacity and malondialdehyde (MDA) levels were measured.Results: Treatment of mice given PTZ with different concentrations of P. crispum extract caused a significant increase in seizure threshold (P < 0.05). In mice receiving PTZ, a significant increase in serum and brain MDA levels was observed (P < 0.05) but no significant change in antioxidant capacity was noticed. Treatment of mice given PTZ with different concentrations of the extract led to a significant increase in brain and serum antioxidant capacity and a significant decrease in brain and serum MDA levels (P < 0.05).Conclusion: P. crispum shows protective efficacy against PTZ-induced seizures, which may be due to its antioxidant effects.